Non-Judicial Procedures of Protecting the Rights of Workers in Belarus, other EEU States and Lithuania* - Tomashevski, Kirill (Teisė, 2021)
The article explores non-judicial mechanisms for labor disputes in Belarus, other Eurasian Economic Union member states (Armenia, Kazakhstan Kyrgyzstan and Russia) and Lithuania in a comparative legal aspect. The author analyzes different procedures for the settlement of individual and collective labor disputes in these countries and puts forward a number of proposals to improve these procedures in the legislation.
Keywords: labor disputes; workers; arbitration; mediation; labor dispute commissions